Internal and External Determinants of Profitability In 50 Banks In Indonesia (2012-2023) - Aditya Rahadi; Valentino Budhidharma (Publikasi Indonesia, 2026)
This research aims to analyze the influence of internal and external factors on bank profitability in Indonesia, measured by Return on Assets (ROA) and Return on Equity (ROE). Bank profitability is a crucial pillar for the sustainability and growth of financial institutions, making it highly essential for operational continuity and the ability to provide financial services. Therefore, in-depth analysis of the factors influencing it is indispensable. The analysis was conducted using data from banks listed on the Indonesia Stock Exchange during the period 2012–2023 with the panel data regression method. The approaches used include the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), along with diagnostic tests such as the Chow Test, Hausman Test, and Lagrange Multiplier Test to determine the best model. The research results indicate that bank profitability is positively and significantly influenced by Net Interest Margin, but negatively and significantly influenced by Total Money Supply and the BI Rate (or interest rates).